Efficacy and safety of enoxaparin versus unfractionated heparin during percutaneous coronary intervention: systematic review and meta-analysis. (3rd February 2012) - Silvain, Johanne; Beygui, Farzin; Barthélémy, Olivier; Pollack, Charles; Cohen, Marc; Zeymer, Uwe; Huber, Kurt; Goldstein, Patrick; Cayla, Guillaume; Collet, Jean-Philippe; Vicaut, Eric; Montalescot, Gilles
Abstract : Objective To determine the efficacy and safety of enoxaparin compared with unfractionated heparin during percutaneous coronary intervention. Design Systematic review and meta-analysis. Data sources Medline and Cochrane database of systematic reviews, January 1996 to May 2011. Study selection Randomised and non-randomised studies comparing enoxaparin with unfractionated heparin during percutaneous coronary intervention and reporting on both mortality (efficacy end point) and major bleeding (safety end point) outcomes. Data extraction Sample size, characteristics, and outcomes, extracted independently and analysed. Data synthesis 23 trials representing 30 966 patients were identified, including 10 243 patients (33.1%) undergoing primary percutaneous coronary intervention for ST elevation myocardial infarction, 8750 (28.2%) undergoing secondary percutaneous coronary intervention after fibrinolysis, and 11 973 (38.7%) with non-ST elevation acute coronary syndrome or stable patients scheduled for percutaneous coronary intervention. A total of 13 943 patients (45.0%) received enoxaparin and 17 023 (55.0%) unfractionated heparin. Enoxaparin was associated with significant reductions in death (relative risk 0.66, 95% confidence interval 0.57 to 0.76; P<0.001), the composite of death or myocardial infarction (0.68, 0.57 to 0.81; P<0.001), and complications of myocardial infarction (0.75, 0.6 to 0.85; P<0.001), and a reduction in incidence of major bleeding (0.80, 0.68 to 0.95; P=0.009). In patients who underwent primary percutaneous coronary intervention, the reduction in death (0.52, 0.42 to 0.64; P<0.001) was particularly significant and associated with a reduction in major bleeding (0.72, 0.56 to 0.93; P=0.01). Conclusion Enoxaparin seems to be superior to unfractionated heparin in reducing mortality and bleeding outcomes during percutaneous coronary intervention and particularly in patients undergoing primary percutaneous coronary intervention for ST elevation myocardial infarction.